The study of using gis tools in sustainable management of solar energy = Studium wykorzystania narzędzi geoinformacyjnych w zrównoważonym gospodarowaniu energią słoneczną - Bujarkiewicz, Adam; Sztubecka, Małgorzata; Sztubecki, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Resource efficiency is the primary element of the European Union`s Europe 2020 strategy for the economic growth. It aims at stimulating economic growth which will be smart, sustainable and inclusive. Proper land use is beneficial to the economic development and it contributes to the improvement of living conditions considering the principle of sustainable development.
Keywords: renewable energy sources; solar potential; solar energy; GIS; odnawialne źródła energii; potencjał solarny; energia słoneczna